Przemiany międzypokoleniowe, mikroewolucja czy długotrwałe fluktuacje przstosowawcze - fakty i opinie - Wolański, Napoleon (Polskie Towarzystwo Antropologiczne, 1987)
The possibility of the realization of the factors mentioned in the title in the human populations were subject to critical discussion on the basis of own assumptions and literature.
Intergenerational changes; microevolution or long-term adaptational fluctuations - facts and views